3D Microtissues Mimic the Architecture, Estradiol Synthesis, and Gap Junction Intercellular Communication of the Avascular Granulosa. (22nd December 2021) - Ip, Blanche C; Leary, Elizabeth; Knorlein, Benjamin; Reich, David; Van, Vivian; Manning, Joshua; Morgan, Jeffrey R
Abstract: Humans are consistently exposed to thousands of untested chemicals that have been detected in the follicular fluid of the ovaries, and can disrupt reproductive health. Human granulosa cells (GCs) are the functional unit of the ovarian follicle with steroidogenic and signaling activities, and play a pivotal role in oocyte development. During follicle progression, GCs multiply to form a 3D avascular structure, and establish gap junction intercellular communication (GJIC) that is critical to maintaining optimal viability and function. We developed a high-throughput in vitro platform of human GCs for the screening of chemicals that can impact GJIC and estradiol (E2) production of human granulosa. Our granulosa 3D microtissues fabricated with human ovarian granulosa-like tumor KGN cells are multicell-layered structures that mimic the avascular granulosa layers surrounding the oocyte. These microtissues robustly expressed the steroidogenic CYP19 aromatase enzyme and GJIC intercellular membrane channel, connexin 43. Granulosa microtissues produced E2 at rates comparable to primary human GCs as previously reported. E2 production was suppressed by the CYP19 inhibitor, letrozole, and induced by CYP19 activators, bisphenol A at 100 µM, and genistein at 100 µM. Granulosa microtissues displayed active GJIC function, as demonstrated by the connexin 43-dependent diffusion of calcein fluorescent dye from microtissue surface to the core using high-throughput confocal microscopy in conjunction with our open-sourced automated image analysis tool. Overall, our 3D human granulosa screening platform is highly promising for predictive and efficient in vitro toxicity testing to screen for chemicals that contaminate follicular fluid and may affect fertility.